Characterization of Selenium Accumulation, Localization and Speciation in Buckwheat–Implications for Biofortification - Jiang, Ying; El Mehdawi, Ali F.; Tripti,; Lima, Leonardo W.; Stonehouse, Gavin; Fakra, Sirine C.; Hu, Yuegao; Qi, Hua; Pilon-Smits, Elizabeth A. H. (Frontiers in Plant Science, 2018)
Buckwheat is an important crop species in areas of selenium (Se) deficiency. To obtain better insight into their Se metabolic properties, common buckwheat (Fagopyrum esculentum) and tartary buckwheat (F. tataricum) were supplied with different concentrations of Se, supplied as selenate, selenite, or Astragalus bisulcatus plant extract (methyl-selenocysteine). Se was supplied at different developmental stages, with different durations, and in the presence or absence of potentially competing ions, sulfate and phosphate. The plants were analyzed for growth, Se uptake, translocation, accumulation, as well as for Se localization and chemical speciation in the seed. Plants of both buckwheat species were supplied with 20 μM of either of the three forms of Se twice over their growth period. Both species accumulated 15-40 mg Se kg-1 DW in seeds, leaves and stems, from all three selenocompounds. X-ray microprobe analysis showed that the Se in seeds was localized in the embryo, in organic C-Se-C form(s) resembling selenomethionine, methyl-selenocysteine and -glutamyl-methylselenocysteine standards. In short-term (2h and 24h) Se uptake studies, both buckwheat species showed higher Se uptake rate and shoot Se accumulation when supplied with plant extract (methyl-selenocysteine), compared to selenite or selenate. In long-term (7d) uptake studies, both species were resistant to selenite up to 50 μM. Tartary buckwheat was also resistant to selenate up to 75 μM Se, but >30 μM selenate inhibited common buckwheat growth. Selenium accumulation was similar in both species. When selenite was supplied, Se levels were 10-20-fold higher in root (up to 900 mg Se kg-1 DW) than shoot, but 4-fold higher in shoot (up to 1,200 mg Se kg-1 DW) than root for selenate-supplied plants. Additionally, sulfate and phosphate supply affected Se uptake, and conversely selenate enhanced S and P accumulation in both species. These findings have relevance for crop Se biofortification applications.